1984
DOI: 10.1029/gl011i009p00923
|View full text |Cite
|
Sign up to set email alerts
|

Dayside red auroras at very high latitudes: The importance of thermal excitation

Abstract: Extensive radar observations have been made from Sondrestrom of the F region in the daytime sector between 70 and 79° Λ. Regions of enhanced electron temperature and electron density are found in close association with the velocity reversal in the morning and afternoon convection cells. From the radar measurements, calculations are made of the contributions to the atomic oxygen emission at 6300A from dissociative recombination and thermal excitation. The latter mechanism, in particular, in the enhancement regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 12 publications
7
21
0
Order By: Relevance
“…Optical emission altitudes for both ionospheric recombination and particle impact ionization have been well studied in the literature, and here we will simply refer the reader to that work. The altitude parameter dependencies of 630.0 nm emissions for a wide range of altitudes and intensity levels have been studied using incoherent scatter radar data applied to several nights' observation at Arecibo for both stable [ Wickwar et al ., ] and perturbed [ Cogger et al ., ] thermospheric conditions and at higher latitudes [ Wickwar and Kofman , ; Pallamraju et al ., ]. The red line recombination component of emission comes from the bottomside of the ionospheric F region peak, where the recombination maximizes, but quenching at the lower altitudes can make the topside contribution important for times of low H max .…”
Section: Calculated 6300 Nm Optical Emissionsmentioning
confidence: 99%
“…Optical emission altitudes for both ionospheric recombination and particle impact ionization have been well studied in the literature, and here we will simply refer the reader to that work. The altitude parameter dependencies of 630.0 nm emissions for a wide range of altitudes and intensity levels have been studied using incoherent scatter radar data applied to several nights' observation at Arecibo for both stable [ Wickwar et al ., ] and perturbed [ Cogger et al ., ] thermospheric conditions and at higher latitudes [ Wickwar and Kofman , ; Pallamraju et al ., ]. The red line recombination component of emission comes from the bottomside of the ionospheric F region peak, where the recombination maximizes, but quenching at the lower altitudes can make the topside contribution important for times of low H max .…”
Section: Calculated 6300 Nm Optical Emissionsmentioning
confidence: 99%
“…The enhanced 630 nm emission in poleward-moving cusp/cleft transients is caused by the hot tail of a heated thermal electron population (Wickwar and Kofman, 1984;Lockwood et al, 1993a). The magnetosheath electron precipitation is responsible for that heating, but not for the direct excitation of the emission.…”
Section: Polar Cap Patchesmentioning
confidence: 99%
“…This is due to the fact that the 1 D 2 electron state is readily excited (1.96 eV above the 3 P doublet ground state), whereas very few atoms are excited to the 1 S 0 (4.17 eV above the 3 P ). The excitation can be largely caused by the elevation of the ionospheric electron temperature such that the electrons on the hot tail of the thermal ionospheric gas are very efficient in exciting the 1 D 2 state (Wickwar and Kofman, 1984;Lockwood et al, 1993a;Davis and Lockwood, 1996). A region of dominant red-line emission was first reported by Sandford (1964).…”
Section: Introductionmentioning
confidence: 99%
“…The electron heating in the cusp region which was invoked above as a major cause of the cusp/cleft aurora was inferred in a statistical survey of the topside ionosphere by Titheridge (1976) and has been directly observed by satellite (Brace et al, 1982;Curtis et al, 1982) and incoherent scatter radar (Wickwar and Kofman, 1984;Watermann et al, 1994;McCrea et al, 2000). With very high time resolution (10 s) measurements, Lockwood et al (1993b) have reported that the cusp electron temperature enhancements can sometimes consist of a series of poleward-moving events, very similar to the behaviour of the red-line auroral transients.…”
Section: Introductionmentioning
confidence: 99%